2019
DOI: 10.1016/j.jpsychires.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Structural connectivity and risk for anhedonia after trauma: A prospective study and replication

Abstract: Anhedonia emerges in some people after psychological trauma, reflected by a loss of interest, diminished affect, and detachment. Structural abnormalities in specific neural pathways at the time of trauma may influence the development of these posttraumatic anhedonia (PTA) symptoms. In this prospective study, we determined whether white matter connectivity at around one month post-trauma predicts PTA and other PTSD symptoms at six months post-trauma. Thirty men and women aged 19-62 were recruited from the emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 78 publications
4
16
0
1
Order By: Relevance
“…Despite growing interest in characterizing white matter decrements that are associated with PTSD, surprisingly little prior research has linked the microstructure of these tracts to PTA. In a previous report, we demonstrated that the presence of PTA, up to 6 months after a traumatic event, was predicted by reduced FA of the uncinate fasciculus (Fani et al, 2019). To our knowledge, this is the only study to directly investigate the relationship of white matter microstructure, including fear‐ and reward‐related circuitry, with PTA.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Despite growing interest in characterizing white matter decrements that are associated with PTSD, surprisingly little prior research has linked the microstructure of these tracts to PTA. In a previous report, we demonstrated that the presence of PTA, up to 6 months after a traumatic event, was predicted by reduced FA of the uncinate fasciculus (Fani et al, 2019). To our knowledge, this is the only study to directly investigate the relationship of white matter microstructure, including fear‐ and reward‐related circuitry, with PTA.…”
Section: Introductionmentioning
confidence: 77%
“…Therefore, 75 participants were included in initial analyses (age: M = 35.24, SD = 12.53; 45 males). A subset (n = 28) of participants in the present study were also included in a previous report of white matter predictors of PTA (Fani et al, 2019). The prior report found that acutely assessed FA of the uncinate fasciculus was a prospective marker of 6‐month PTA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating brain structure in recently traumatized individuals and patients with recent-onset PTSD have mostly recruited survivors of fire accidents (Li et al, 2006 ), accidents (Wignall et al, 2004 ) and coalmine-flood disaster (Chen et al, 2012 ; Liu, Li, Luo, Lu, & Yin, 2012 ; Qi et al, 2013 ; Zhang et al, 2011 ). Few studies have investigated brain structure in victims of interpersonal violence in an early state after trauma exposure such as Fani et al ( 2019 ). As to our knowledge, the association between expressive suppression as well as cognitive reappraisal and brain structure has not been investigated in recently trauma-exposed individuals so far.…”
Section: Introductionmentioning
confidence: 99%
“…psychiatric comorbidities, suicidal ideation, hostility, functioning and quality of life, Pietrzak et al, 2015 ), neuroimaging (e.g. the integrity of the uncinate fasciculus, Fani et al, 2019 ), and genetic variables (e.g. 5-HTTLPR genotype, Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%